Development of double heterojunction of Pr2Sn2O7@Bi2Sn2O7/TiO2 for hydrogen production. (July 2020) - Li, Yuejun; Cao, Tieping; Mei, Zemin; Li, Xiaoping; Sun, Dawei
Abstract: The double heterojunction of Pr2 Sn2 O7 @Bi2 Sn2 O7 /TiO2 composite was prepared by one-step hydrothermal method using TiO2 electrospun nanofibers as substrate. The structures were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, ultraviolet (UV)-visible diffuse reflectance spectroscopy and photoluminescence. The performance of photocatalytic hydrogen production over the composite catalyst was studied under UV–visible light. The Pr2 Sn2 O7 @Bi2 Sn2 O7 /TiO2 composite nanofibers showed high photocatalytic activity for hydrogen production. The hydrogen production rate reached 587.1 μmol h −1 g −1, which was 2.7 and 7.1 times that of Bi2 Sn2 O7 /TiO2 and TiO2, respectively. The main reasons for the high photocatalytic activity included broadened spectral range, 4f–4f transition from Pr 3+ of Pr2 Sn2 O7 and increased separation of the photogenerated carriers by double heterojunction via direct Z-scheme transfer. Highlights: Pr2 Sn2 O7 and Bi2 Sn2 O7 can be simultaneously grown on TiO2 nanofibers. Pr2 Sn2 O7 @Bi2 Sn2 O7 /TiO2 double heterojunction can be obtained. The double heterojunction is more active than single heterojunction. Higher activity for hydrogen evolution is observed over double heterojunction.